Survei Kebugaran Jasmani Siswa di SMA Negeri 5 Malang - Dina Surfiyah; Ari Wibowo Kurniawan (Journal Sport Science Indonesia, 2023)
Physical fitness is an important component for students to have as part of their growth and development during the learning process. The COVID-19 that occurred in Indonesia actually caused students to be less movemant. It is no longer surprising that the lack of movement makes students' physical activity decrease so that they are prone to having less physical fitness. The purpose of this study was to find out how the physical fitness of students at SMA Negeri 5 Malang contributes to learning outcome. This research uses a quantitative descriptive type with a survey method. The population in this study were students of classes X, XI, and XII of SMA Negeri 5 Malang, totaling 1,136 students. The sampling technique used was purposive sampling. The sample in this study was 92 students, including 57 girls and 35 boys, who were selected from the sampling based on inclusion and exclusion criteria. Student physical fitness data was taken using the Indonesian Physical Fitness Test (TKJI) instrument. The analysis of the test results is based on the classification norm for each component indicator of the test performed. The results showed that physical fitness was in the lower classification. It is known that the results of students' physical fitness are lacking it is hoped that physical education, sports, and health teachers will evaluate or provide various sports learning media to students so that physical fitness can increase. Keyword: physical fitness, physical education